Hexagonal boron nitride-containing ceramic with consistent longitudinal and radial mechanical properties but obviously different physical properties and preparation method thereof

Through specific raw material ratio and sintering process adjustment, hexagonal boron nitride-based ceramics with consistent longitudinal and radial mechanical properties but significantly different physical properties were successfully prepared, which solved the anisotropy of traditional BN-based ceramics and improved the performance and reliability of the material under complex stress environments.

CN119775021APending Publication Date: 2025-04-08WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411849204.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The BN-based ceramics obtained by traditional preparation methods have anisotropy, resulting in significant differences in their mechanical properties and physical properties in different directions, limiting their use in application scenarios with multi-directional load-bearing capacity requirements.

Method used

Through specific raw material selection, sintering process adjustment, microstructure regulation and processing scheme design, discharge plasma sintering or hot press sintering technology is used to adjust the sintering temperature and pressure process parameters, so as to achieve the preparation of hexagonal boron nitride-based ceramics with consistent longitudinal and radial mechanical properties but significantly different physical properties.

Benefits of technology

The consistency between longitudinal and radial mechanical properties is achieved, and significant differences in physical properties are shown, which enhances the advantages of the material in complex stress environments, reduces the risks of stress concentration and material failure, and improves the reliability and service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775021A_ABST
    Figure CN119775021A_ABST
Patent Text Reader

Abstract

The invention relates to the field of non-oxide structural ceramics, in particular to a hexagonal boron nitride-based ceramic with consistent longitudinal and radial mechanical properties but significantly different physical properties and a preparation method thereof. The target ceramic is successfully prepared by adopting a specific raw material ratio, including C powder, Al powder, B powder and the like, according to a specific chemical equation, and combining spark plasma sintering and hot pressed sintering processes. Through specific raw material selection, sintering process adjustment, microstructure regulation and control and processing scheme design, the hexagonal boron nitride-based ceramic with consistent mechanical properties and significantly different physical properties is successfully prepared, and a technical support is provided for wider industrial application of the hexagonal boron nitride-based ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of non-oxide structural ceramics, and in particular to a hexagonal boron nitride-based ceramic having consistent longitudinal and radial mechanical properties but significantly different physical properties and a preparation method thereof. Background Art

[0002] Boron nitride (BN) has broad application prospects in aerospace, electronic packaging, nuclear industry and other fields due to its excellent high temperature resistance, chemical stability, thermal shock resistance, high thermal conductivity, low dielectric constant and good neutron absorption ability. However, due to the characteristics of its lamellar crystal structure, BN-based ceramics obtained by traditional preparation methods often show obvious anisotropy. Specifically, its physical and mechanical properties (such as strength, toughness, electrical conductivity and thermal conductivity, etc.) vary significantly in different directions. For example, the strength and toughness parallel to the hot pressing direction are higher, while the strength and toughness perpendicular to the hot pressing direction are lower. This anisotropy limits the use of BN-based ceramics in some application scenarios that require multi-directional bearing capacity.

[0003] Although there are some methods that attempt to achieve isotropy of BN-based ceramics by adding sintering aids, using reaction sintering, and optimizing particle size and morphology, these methods often bring certain constraints to the optimization of other physical properties in some cases. In some application scenarios, although there is a requirement for consistency in mechanical properties in different directions, the differences in the physical properties of BN-based ceramics in different directions may bring unique advantages. For example, some electronic substrates need to have better insulation in the direction perpendicular to the base surface (longitudinal) while maintaining similar mechanical properties in different directions, and have higher thermal conductivity in the direction parallel to the base surface (radial). Therefore, how to cleverly balance and optimize the differences in its physical properties while ensuring the consistency of the mechanical properties of the material in different directions has become a key challenge in material design.

[0004] Finally, the complexity and cost of the preparation process also restrict the practical application of these methods. Therefore, developing a simple, efficient and low-cost method to prepare BN-based ceramics with consistent longitudinal and radial mechanical properties but significantly different physical properties remains an important research direction. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a hexagonal boron nitride-based ceramic with consistent mechanical properties in the longitudinal and radial directions but significantly different physical properties and a preparation method thereof. The present invention successfully prepares a hexagonal boron nitride-based ceramic with consistent mechanical properties in the longitudinal and radial directions but significantly different physical properties through specific raw material selection, sintering process adjustment, microstructure regulation and processing scheme design, providing technical support for its wider industrial applications.

[0006] To achieve the above object, the present invention is implemented by the following technical solutions:

[0007] The present invention provides a hexagonal boron nitride-based ceramic having consistent mechanical properties in the longitudinal direction and radial direction but significantly different physical properties, wherein the ceramic is composed of C powder, Al powder, B powder, Si powder, BN powder, MN powder, ZrO 2 Powder, Al 2 O 3 Powder, MC powder, MSi 2 Powder, B 4 C powder, MB 2 Powder, SiC powder, Si 3 N 4 The powder is used as the raw material, and the powder raw material ratio is determined according to any one of the following chemical reaction equations (1) to (11):

[0008] 3MN+Al+8B+5.98BN=3MB 2 +AlN+7.98BN (1)

[0009] 4MN+3Si+4B 4 C+3BN=3MB 2 +3SiC+7BN (2)

[0010] Si 3 N 4 +2C+B 4 C+BN=3SiC+5BN (3)

[0011] MN+3B+3BN=MB 2 +4BN (4)

[0012] MSi 2 +5BN=MSi 2 +5BN (5)

[0013] MC+6BN=MC+6BN (6)

[0014] ZrO 2 +4BN=ZrO 2 +4BN (7)

[0015] Al 2 O 3 +4BN=Al 2 O 3 +4BN (8)

[0016] Si 3 N 4 +6BN=Si 3 N 4 +6BN (9)

[0017] SiC+5BN= SiC+5BN (10)

[0018] MB 2 +SiC+7BN=MB 2 +SiC+7BN (11)

[0019] Wherein, M is selected from any one of Zr, Hf, Nb, Ta, Ti, W, V, Cr and Mo.

[0020] The present invention is based on the raw material formula and ratio provided by the above 11 equations, and adjusts the sintering temperature, pressure and other process parameters through spark plasma sintering or hot pressing sintering technology to achieve material densification and hBN platelets oriented in the direction perpendicular to the pressure, and the orientation index (lottering factor) of the BN grains is not less than 0.9. On the basis of having texture characteristics, the material can be cut along the selected geometric orientation, so as to finally obtain BN-based ceramics with consistent mechanical properties in the radial and longitudinal directions, but different physical properties.

[0021] According to equations (1) to (4), the consistency of mechanical properties and uniformity of crystal structure of BN-based ceramics, MB 2 The interface strength between AlN, SiC and BN is closely related. When multiple materials are fully combined, the layered structure of BN is evenly distributed, and the self-propagating reaction helps to form a uniform phase distribution, avoiding excessive accumulation of specific phases in certain directions and achieving consistency in mechanical properties. However, the thermal conductivity and electrical conductivity of BN along the layer direction are quite different from those perpendicular to the layer direction, and MB 2 There is a big gap between the physical properties of AlN and SiC, especially MB 2 , SiC and BN each have different thermal expansion coefficients, which will cause large differences in physical properties such as thermal conductivity and electrical conductivity in different directions.

[0022] According to equations (5) to (11), after adding the second phase as an additive and sintering at high temperature, the grains of BN-based ceramics are small and evenly distributed, making the mechanical properties of the material consistent in different directions. However, the thermal conductivity and electrical conductivity of BN are large in the plane direction, while the thermal conductivity perpendicular to the plane is poor, and the asymmetry of the temperature gradient or particle flow, the interface characteristics of BN and the second phase, and their interaction will lead to differences in physical properties.

[0023] As a further optimization scheme of the present invention, the average particle size of the MN powder is 0.5-10 μm, and the purity is >95%; 4 The average particle size of the C powder is 1-10 μm, and the purity is >95%; the average particle size of the Si powder is 0.5-5 μm, and the purity is >95%; the ZrO 2 The average particle size of the powder is 0.5-10 μm, and the purity is >95%. 2 O 3 The average particle size of the powder is 0.5-5 μm, and the purity is >95%; the average particle size of the Al powder is 0.1-10 μm, and the purity is >95%; the average particle size of the MC powder is 0.5-10 μm, and the purity is >95%; the average particle size of the B powder is 0.2-10 μm, and the purity is ≥95%; the average particle size of the BN powder is 1-10 μm, and the purity is >95%; the MB 2 The average particle size of the powder is 0.2-10 μm, and the purity is >95%. 2 The average particle size of the powder is 0.5 to 10 μm, and the purity is >95%; the average particle size of the SiC powder is 0.5 to 10 μm, and the purity is >95%; 3 N 4 The average particle size of the powder is 0.2-10 μm, and the purity is >95%; the average particle size of the C powder is 0.5-10 μm, and the purity is >95%.

[0024] On the other hand, the present invention provides a hexagonal boron nitride-based ceramic having consistent mechanical properties in the longitudinal direction and radial direction but significantly different physical properties and a preparation method thereof, comprising the following steps:

[0025] Step 1: Material preparation: mix the powder raw materials according to the chemical reaction equation, evenly mix, dry, grind and sieve the mixed powders to obtain sintered raw material powders;

[0026] As a further optimization scheme of the present invention, in step 1, anhydrous ethanol and zirconium oxide balls are used as ball milling media, and the mass ratio of powder to ball is 1:(1.5-2). The proportioned powder is evenly mixed for 20-30 hours, and the slurry after rotary evaporation is dried in a vacuum drying oven at 50-70°C, and the sintered raw material powder is obtained after grinding and sieving.

[0027] Step 2: Spark plasma sintering (SPS) or hot pressing sintering. The weight of the required sintered powder is calculated according to the required sample thickness. The sieved powder is poured into a graphite mold and sintered in a vacuum environment to obtain a cylindrical sintered body containing hexagonal boron nitride-based ceramics.

[0028] As a further optimization solution of the present invention, in step 2, the thickness of the sintered sample is 20 to 40 mm.

[0029] As a further optimization scheme of the present invention, in step 2, by optimizing the sintering process parameters, the hBN sheets are oriented in the composite material along the direction perpendicular to the pressure, and the grain orientation index (lottering factor) thereof is not less than 0.9.

[0030] As a further optimization scheme of the present invention, in step 2, the sintering temperature ranges from 1400°C to 2000°C.

[0031] As a further optimization scheme of the present invention, in step 2, the sintering heating rate is 10-300°C / min.

[0032] As a further optimization scheme of the present invention, in step 2, the pressure applied by the sintering equipment is 20 to 200 MPa.

[0033] As a further optimization scheme of the present invention, in step 2, the sintering holding time is 5 to 90 minutes.

[0034] As a further optimization scheme of the present invention, in step 2, the inner wall of the graphite mold sleeve and the powder are separated by graphite paper with a thickness of 0.2 mm.

[0035] The specific process of spark plasma sintering (SPS) or hot pressing sintering is to heat the mixed raw material powder to 1400℃~2000℃ at a heating rate of 10-300℃ / min, and then keep it at this temperature for 5~90min, wherein the sintering pressure is 20~200MPa, and the pressure is applied before the start of heating, and the pressure is maintained until the end of sintering. By changing the parameters such as sintering temperature, holding time, loading pressure and heating rate, the densification of ceramics and the complete orientation of BN lamellae in the direction perpendicular to the pressure are achieved, and the orientation index (lottering factor) of BN grains is not less than 0.9.

[0036] Step 3: After sintering, the cylindrical sintered body is finely processed into an elliptical cylindrical sample according to a preset angle θ (0°<θ<90°), and then the horizontally placed elliptical cylindrical sample is further processed along its longitudinal and radial directions to obtain a hexagonal boron nitride-based ceramic product of a preset shape and size.

[0037] The technical solution provided by the present invention has the following beneficial effects:

[0038] 1. The longitudinal and radial mechanical properties are consistent, but the physical properties are significantly different: On the basis of the consistency of the longitudinal and radial mechanical properties (bending strength and compressive strength), the physical properties of BN-based ceramics are different ( Figure 2-Figure 3 ). This balance of performance enables the material to perform better in complex stress environments, reduces the risk of stress concentration and material failure caused by anisotropy, improves the reliability and service life of the material, and provides flexible solutions for material needs in different fields.

[0039] 2. Simplified process of material preparation and processing: Compared with the traditional isotropic improvement method, the process flow adopted by the present invention simplifies the material preparation and processing process, and reduces the manufacturing cost. At the same time, the method is applicable to a variety of BN-based ceramic material systems, has good process compatibility and scalability, and is convenient for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 It is a flow chart of preparation and performance testing;

[0041] Figure 2 The longitudinal and radial electrical and thermal conductivities of the sample when the cutting angle θ is 30° in Example 1;

[0042] Figure 3 The longitudinal and radial electrical and thermal conductivities of the sample when the cutting angle θ is 60° in Example 11;

[0043] Figure 4 The morphology of the sample in Example 1 after bending and breaking at different angles. DETAILED DESCRIPTION

[0044] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred implementation scheme of the present invention is described below in conjunction with specific embodiments, but it should not be understood as limiting the present invention and is only used as an example.

[0045] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.

[0046] The invention aims to be achieved by the present invention as follows: (1) Realization of consistent longitudinal and radial mechanical properties but significant differences in physical properties: Under the premise of ensuring the consistency of mechanical properties of BN-based ceramics, the difference in physical properties is achieved to meet the requirements of different application environments and improve the reliability and applicability of materials in practical applications. (2) Optimization of material composition and processing technology: Explore suitable material composition, develop simple, efficient and low-cost preparation processes, and design and regulate microstructures to produce BN-based ceramics with consistent mechanical properties but significant differences in physical properties, and ensure the overall mechanical properties and stability of the material.

[0047] To achieve the above object, the present invention provides a hexagonal boron nitride-based ceramic having consistent mechanical properties in the longitudinal direction and radial direction but significantly different physical properties and a preparation method thereof, which specifically comprises the following steps:

[0048] Step 1, material preparation: Use commercially available powder as raw material, and mix the powder according to the following chemical reaction equation; mix them evenly in a ball mill for 24 hours in a certain proportion, use anhydrous ethanol and zirconium oxide balls as ball milling media, and the mass ratio of material to ball is 1:(1.5-2). The slurry after rotary evaporation is dried in a vacuum drying oven at 50-70°C to obtain sintered raw material powder.

[0049] 3MN+Al+8B+5.98BN=3MB 2 +AlN+7.98BN (1)

[0050] 4MN+3Si+4B 4 C+3BN=3MB 2 +3SiC+7BN (2)

[0051] Si 3 N 4 +2C+B 4 C+BN=3SiC+5BN (3)

[0052] MN+3B+3BN=MB 2 +4BN (4)

[0053] MSi 2 +5BN=MSi 2 +5BN (5)

[0054] MC+6BN=MC+6BN (6)

[0055] ZrO 2 +4BN=ZrO 2 +4BN (7)

[0056] Al 2 O 3+4BN=Al 2 O 3 +4BN (8)

[0057] Si 3 N 4 +6BN=Si 3 N 4 +6BN (9)

[0058] SiC+5BN= SiC+5BN (10)

[0059] MB 2 +SiC+7BN=MB 2 +SiC+7BN (11)

[0060] Wherein, M is selected from any one of Zr, Hf, Nb, Ta, Ti, W, V, Cr and Mo.

[0061] The average particle size of MN powder is 0.5-10 μm, and the purity is >95%. 4 The average particle size of the C powder is 1-10 μm, and the purity is >95%; the average particle size of the Si powder is 0.5-5 μm, and the purity is >95%; the ZrO 2 The average particle size of the powder is 0.5-10 μm, and the purity is >95%. 2 O 3 The average particle size of the powder is 0.5-5 μm, and the purity is >95%; the average particle size of the Al powder is 0.1-10 μm, and the purity is >95%; the average particle size of the MC powder is 0.5-10 μm, and the purity is >95%; the average particle size of the B powder is 0.2-10 μm, and the purity is ≥95%; the average particle size of the BN powder is 1-10 μm, and the purity is >95%; the MB 2 The average particle size of the powder is 0.2-10 μm, and the purity is >95%. 2 The average particle size of the powder is 0.5 to 10 μm, and the purity is >95%; the average particle size of the SiC powder is 0.5 to 10 μm, and the purity is >95%; 3 N 4 The average particle size of the powder is 0.2-10 μm, and the purity is >95%; the average particle size of the C powder is 0.5-10 μm, and the purity is >95%.

[0062] Step 2, spark plasma sintering (SPS) or hot pressing sintering: according to the required sample thickness (20-40 mm), calculate the weight of the required sintering powder, pour the sieved powder into the corresponding graphite mold, separate the inner wall of the mold sleeve and the powder with a graphite paper with a thickness of 0.2 mm, and sinter in a vacuum environment. By changing the sintering temperature, holding time, loading pressure, heating rate and other parameters, the densification of the ceramic and the complete orientation of the BN lamellae in the direction perpendicular to the pressure are achieved, and the grain orientation index (lottering factor) is not less than 0.9.

[0063] The thickness of the sintered sample in step 2 is 20 to 40 mm.

[0064] The sintering temperature in step 2 ranges from 1400°C to 2000°C.

[0065] In step 2, the sintering heating rate is 10-300°C / min.

[0066] In step 2, the pressure applied by the sintering equipment is 20 to 200 MPa.

[0067] The sintering holding time in step 2 is 5 to 90 minutes.

[0068] In step 2, the inner wall of the sintering mold sleeve and the powder are separated by graphite paper with a thickness of 0.2 mm.

[0069] The specific process of spark plasma sintering or hot pressing sintering is to heat the mixed raw material powder to 1400℃~2000℃ at a heating rate of 10-300℃ / min, and then keep it at this temperature for 5-90min, wherein the sintering pressure is 20-200MPa, and the pressure is applied before starting to heat up and maintained until the end of sintering.

[0070] Step 3: After sintering, the cylindrical sintered body is finely processed into an elliptical cylindrical sample according to a preset angle θ (0°<θ<90°), and then the horizontally placed elliptical cylindrical sample is further processed in the longitudinal and radial directions to obtain a hexagonal boron nitride-based ceramic product of a preset shape and size.

[0071] In order to further verify the product performance obtained in step 3, the preset angle θ is set to 30°, 45°, 50°, and 60° respectively, and the samples corresponding to the preset angles are cut according to the method of step 3. Then, the mechanical properties (bending strength and compression strength) and physical properties (electrical conductivity and thermal conductivity) of different samples are tested. The test results are shown in Examples 1-11. The detailed process of the entire preparation and performance test is as follows Figure 1 shown.

[0072] The following embodiments are combined with the accompanying drawings to further illustrate the technical solution of the present invention, but are not intended to limit the protection scope of the present invention.

[0073] Example 1

[0074] TiN powder, Al powder, B powder and BN powder are used as raw materials and are prepared according to equation (1).

[0075] The phase composition (volume content) of the obtained sample is 60% BN-32% TiB 2 -8% AlN.

[0076] With anhydrous ethanol and zirconium oxide balls as ball milling media, TiN, Al, B and BN are uniformly mixed according to the stoichiometric ratio, then rotary evaporated, dried, ground and sieved, and finally poured into the SPS graphite mold. The inner wall of the mold sleeve and the powder are separated by a 0.2mm thick graphite paper. The temperature is raised to 400℃, and the pressure applied to the sample is 60MPa. The sample is heated to 1850℃ at a rate of 100℃ / min and maintained at 1850℃ and 60MPa for 20min. Finally, the pressure is reduced to 3MPa and the heating is stopped. The sample is cooled to room temperature with the furnace. The relative density of the obtained ceramic is 98.1%, and the hBN grain orientation index is 0.92. When the cutting angle θ is 30°, the room temperature flexural strength of the sample in the radial and longitudinal directions is 254±13MPa and 239±25MPa, respectively; the room temperature compressive strength of the sample in the radial and longitudinal directions is 352±22MPa and 338±31MPa, respectively; the room temperature electrical conductivity of the sample in the radial and longitudinal directions is 2.12×10 5 S / m and 5.18×10 5 S / m; the room temperature thermal conductivity of the sample in the radial and longitudinal directions is 74.25W / mK and 30.12W / mK respectively; the electrical conductivity and thermal conductivity of the sample in the radial and longitudinal directions at different temperatures are as follows Figure 2 By cutting at multiple angles such as 0°, 30°, 45°, 60° and 90°, combined with SEM image observation of the fracture morphology, it can be found that the BN sheets in the dense material are arranged regularly in the sintering pressure direction (such as Figure 4 This ordered arrangement provides the basis for achieving consistency in mechanical properties and differentiation in physical properties.

[0077] Example 2

[0078] TiN powder, Si powder, B 4 C powder and BN powder are used as raw materials and are prepared according to equation (2).

[0079] The phase composition (volume content) of the obtained sample is 48% BN-29% TiB 2 -23% SiC.

[0080] Anhydrous ethanol and zirconium oxide balls were used as ball milling media. TiN, Si, B 4 After the four powders of C and BN powder were evenly mixed, they were rotary evaporated, dried, ground and sieved, and finally poured into the hot-pressed graphite mold. The inner wall of the mold sleeve and the powder were separated by a 0.2mm thick graphite paper. During hot-pressing sintering, the pressure applied to the sample was 30MPa, and the sample was heated to 1700℃ at a rate of 10℃ / min, and maintained at 1700℃ and 30MPa for 90min. Finally, the pressure was reduced to 3MPa and the heating was stopped. The sample was cooled to room temperature with the furnace. The relative density of the obtained ceramic was 98.5%, and the hBN grain orientation index was 0.94. When the cutting angle θ was 30°, the room temperature flexural strength of the sample in the radial and longitudinal directions was 485±17MPa and 501±27MPa, respectively; the room temperature compressive strength of the sample in the radial and longitudinal directions was 503±24MPa and 489±37MPa, respectively; the room temperature conductivity of the sample in the radial and longitudinal directions was 0.78×10 5 S / m and 3.23×10 5 S / m; the room temperature thermal conductivities of the sample in the radial and longitudinal directions are 44.85 W / mK and 20.98 W / mK, respectively.

[0081] Example 3

[0082] Si 3 N 4 powder, C powder, B 4 C powder and BN powder are used as raw materials and are prepared according to equation (3).

[0083] The phase composition (volume content) of the obtained sample is 60% BN-40% SiC.

[0084] Anhydrous ethanol and zirconium oxide balls were used as ball milling media. 3 N 4 , C, B 4After the four powders of C and BN were evenly mixed, they were rotary evaporated, dried, ground and sieved, and finally poured into the graphite mold of SPS. The inner wall of the mold sleeve and the powder were separated by a graphite paper with a thickness of 0.2 mm. The temperature was raised to 400 ° C, and the pressure applied to the sample was 100 MPa. The sample was heated to 1900 ° C at a rate of 100 ° C / min and maintained at 1900 ° C and 100 MPa for 20 minutes. Finally, the pressure was reduced to 3 MPa and the heating was stopped. The sample was cooled to room temperature with the furnace. The relative density of the obtained ceramic was 98.5%, and the hBN grain orientation index was 0.93. When the cutting angle θ was 45 °, the room temperature bending strength of the sample in the radial and longitudinal directions was 382 ± 17 MPa and 399 ± 20 MPa, respectively; the room temperature compressive strength of the sample in the radial and longitudinal directions was 411 ± 12 MPa and 420 ± 16 MPa, respectively; the room temperature conductivity of the sample in the radial and longitudinal directions was 0.21 × 10 5 S / m and 2.81×10 5 S / m; the room temperature thermal conductivities of the sample in the radial and longitudinal directions are 77.14 W / mK and 38.25 W / mK, respectively.

[0085] Example 4

[0086] VN powder, B powder and BN powder are used as raw materials and the ingredients are prepared according to equation (4).

[0087] The sample phase composition (volume content) is 74% BN-26% VB 2 .

[0088] Using anhydrous ethanol and zirconium oxide balls as ball milling media, the three powders of VN, B and BN according to the stoichiometric ratio are evenly mixed, then rotary evaporated, dried, ground and sieved, and finally poured into a hot-pressed graphite mold. The inner wall of the mold sleeve and the powder are separated by a 0.2mm thick graphite paper. Through hot-pressing sintering, the pressure applied to the sample is 50MPa, the sample is heated to 1900℃ at a rate of 10℃ / min, and maintained at 1900℃ and 50MPa for 60min. Finally, the pressure is reduced to 3MPa and the heating is stopped. The sample is cooled to room temperature with the furnace. The relative density of the obtained ceramic is 98.2%, and the hBN grain orientation index is 0.95. When the cutting angle θ is 45°, the room temperature flexural strength of the sample in the radial and longitudinal directions is 273±22MPa and 270±5MPa, respectively; the room temperature compressive strength of the sample in the radial and longitudinal directions is 232±27MPa and 244±12MPa, respectively; the room temperature electrical conductivity of the sample in the radial and longitudinal directions is 1.53×10 5 S / m and 4.6×10 5 S / m; the room temperature thermal conductivities of the sample in the radial and longitudinal directions are 13.42 W / mK and 44.22 W / mK, respectively.

[0089] Example 5

[0090] TaSi 2 Powder and BN powder are used as raw materials and the ingredients are prepared according to equation (5).

[0091] The sample phase composition (volume content) is 66% BN-34% TaSi 2 .

[0092] Anhydrous ethanol and zirconium oxide balls were used as ball milling media. TaSi 2 After the two powders of HN and BN are evenly mixed, they are rotary evaporated, dried, ground and sieved, and finally poured into the graphite mold of SPS. The inner wall of the mold sleeve and the powder are separated by a 0.2mm thick graphite paper. Through hot pressing sintering, the pressure applied to the sample is 200MPa, the sample is heated to 2000℃ at a rate of 100℃ / min, and maintained at 2000℃ and 200MPa for 10min. Finally, the pressure is reduced to 3MPa and the heating is stopped. The sample is cooled to room temperature with the furnace. The relative density of the obtained ceramic is 98.8%, and the hBN grain orientation index is 0.91. When the cutting angle θ is 50°, the room temperature bending strength of the sample in the radial and longitudinal directions is 333±25MPa and 342±12MPa, respectively; the room temperature compressive strength of the sample in the radial and longitudinal directions is 425±12MPa and 411±23MPa, respectively; the room temperature conductivity of the sample in the radial and longitudinal directions is 0.75×10 5 S / m and 3.1×10 5 S / m; the room temperature thermal conductivities of the sample in the radial and longitudinal directions are 13.25 W / mK and 43.02 W / mK, respectively.

[0093] Example 6

[0094] MoC powder and BN powder are used as raw materials and the ingredients are prepared according to equation (6).

[0095] The phase composition (volume content) of the obtained sample is 85% BN-15% MoC.

[0096] Using anhydrous ethanol and zirconium oxide balls as ball milling media, the two powders of MoC and BN according to the stoichiometric ratio are evenly mixed, then rotary evaporated, dried, ground and sieved, and finally poured into the SPS graphite mold. The inner wall of the mold sleeve and the powder are separated by a 0.2mm thick graphite paper. Through hot pressing sintering, the pressure applied to the sample is 150MPa, the sample is heated to 2000℃ at a rate of 100℃ / min, and maintained at 2000℃ and 150MPa for 15min. Finally, the pressure is reduced to 3MPa and the heating is stopped. The sample is cooled to room temperature with the furnace. The relative density of the obtained ceramic is 98.8%, and the hBN grain orientation index is 0.96. When the cutting angle θ is 50°, the room temperature flexural strength of the sample in the radial and longitudinal directions is 442±27MPa and 440±32MPa, respectively; the room temperature compressive strength of the sample in the radial and longitudinal directions is 520±17MPa and 526±20MPa, respectively; the room temperature electrical conductivity of the sample in the radial and longitudinal directions is 0.65×10 5 S / m and 2.17×10 5 S / m; the room temperature thermal conductivities of the sample in the radial and longitudinal directions are 23.28 W / mK and 53.12 W / mK, respectively.

[0097] Example 7

[0098] Si 3 N 4 Powder and BN powder are used as raw materials and the ingredients are prepared according to equation (9).

[0099] The sample phase composition (volume content) is 60% BN-40% Si 3 N 4 .

[0100] Anhydrous ethanol and zirconium oxide balls were used as ball milling media. 3 N 4 After the two powders of HN and BN are evenly mixed, they are rotary evaporated, dried, ground and sieved, and finally poured into the graphite mold of SPS. The inner wall of the mold sleeve and the powder are separated by a 0.2mm thick graphite paper. The temperature is raised to 400℃, and the pressure applied to the sample is 200MPa. The sample is heated to 2000℃ at a rate of 100℃ / min and maintained at 2000℃ and 200MPa for 10min. Finally, the pressure is reduced to 3MPa and the heating is stopped. The sample is cooled to room temperature with the furnace. The relative density of the obtained ceramic is 98.2%, and the hBN grain orientation index is 0.92. When the cutting angle θ is 45°, the room temperature bending strength of the sample in the radial and longitudinal directions is 252±23MPa and 260±15MPa, respectively; the room temperature compressive strength of the sample in the radial and longitudinal directions is 202±17MPa and 207±22MPa, respectively; the room temperature conductivity of the sample in the radial and longitudinal directions is 0.25×105 S / m and 2.55×10 5 S / m; the room temperature thermal conductivities of the sample in the radial and longitudinal directions are 83.25 W / mK and 44.87 W / mK, respectively.

[0101] Example 8

[0102] SiC powder and BN powder are used as raw materials and the ingredients are prepared according to equation (10).

[0103] The phase composition (volume content) of the obtained sample is 82% BN-18% SiC.

[0104] With anhydrous ethanol and zirconium oxide balls as ball milling media, SiC and BN powders according to the stoichiometric ratio are uniformly mixed, then rotary evaporated, dried, ground and sieved, and finally poured into a hot-pressed graphite mold. The inner wall of the mold sleeve and the powder are separated by a 0.2 mm thick graphite paper. To increase the hot-pressing sintering, the pressure applied to the sample is 30 MPa, the sample is heated to 2000 ° C at a rate of 10 ° C / min, and maintained at 2000 ° C and 30 MPa for 60 minutes, and finally the pressure is reduced to 3 MPa and the heating is stopped, and the sample is cooled to room temperature with the furnace. The relative density of the obtained ceramic is 98.4%, and the hBN grain orientation index is 0.94. When the cutting angle θ is 60°, the room temperature flexural strength of the sample in the radial and longitudinal directions is 202±15MPa and 200±19MPa, respectively; the room temperature compressive strength of the sample in the radial and longitudinal directions is 175±29MPa and 197±23MPa, respectively; the room temperature electrical conductivity of the sample in the radial and longitudinal directions is 0.21×10 5 S / m and 2.02×10 5 S / m; the room temperature thermal conductivities of the sample in the radial and longitudinal directions are 23.17 W / mK and 41.47 W / mK, respectively.

[0105] Example 9

[0106] With ZrO 2 Powder and BN powder are used as raw materials and the ingredients are prepared according to equation (7).

[0107] The sample phase composition (volume content) is 68% BN-32% ZrO 2 .

[0108] Anhydrous ethanol and zirconium oxide balls were used as ball milling media. ZrO 2After the two powders of hBN and BN are evenly mixed, they are rotary evaporated, dried, ground and sieved, and finally poured into the graphite mold of SPS. The inner wall of the mold sleeve and the powder are separated by a 0.2mm thick graphite paper. The temperature is raised to 400℃, and the pressure applied to the sample is 180MPa. The sample is heated to 2000℃ at a rate of 100℃ / min and maintained at 2000℃ and 180MPa for 15min. Finally, the pressure is reduced to 3MPa and the heating is stopped. The sample is cooled to room temperature with the furnace. The relative density of the obtained ceramic is 98.4%, and the hBN grain orientation index is 0.95. When the cutting angle θ is 60°, the room temperature bending strength of the sample in the radial and longitudinal directions is 232±19MPa and 249±22MPa, respectively; the room temperature compressive strength of the sample in the radial and longitudinal directions is 205±20MPa and 207±16MPa, respectively; the radial and longitudinal room temperature conductivity of the sample is 0.14×10 5 S / m and 2.54×10 5 S / m; the room temperature thermal conductivities of the sample in the radial and longitudinal directions are 10.38 W / mK and 32.25 W / mK, respectively.

[0109] Example 10

[0110] Al 2 O 3 Powder and BN powder are used as raw materials and the ingredients are prepared according to equation (8).

[0111] The phase composition (volume content) of the obtained sample is 60% BN-40% Al 2 O 3 .

[0112] Using anhydrous ethanol and zirconium oxide balls as ball milling media, Al 2 O 3 After the two powders of HN and BN are evenly mixed, they are rotary evaporated, dried, ground and sieved, and finally poured into the graphite mold of SPS. The inner wall of the mold sleeve and the powder are separated by a 0.2mm thick graphite paper. The temperature is raised to 400℃, and the pressure applied to the sample is 180MPa. The sample is heated to 2000℃ at a rate of 100℃ / min and maintained at 2000℃ and 180MPa for 15min. Finally, the pressure is reduced to 3MPa and the heating is stopped. The sample is cooled to room temperature with the furnace. The relative density of the obtained ceramic is 98.4%, and the hBN grain orientation index is 0.93. When the cutting angle θ is 60°, the room temperature bending strength of the sample in the radial and longitudinal directions is 520±15MPa and 510±22MPa, respectively; the room temperature compressive strength of the sample in the radial and longitudinal directions is 657±20MPa and 666±11MPa, respectively; the radial and longitudinal room temperature conductivity of the sample is 0.31×10 5 S / m and 2.92×105 S / m; the room temperature thermal conductivities of the sample in the radial and longitudinal directions are 14.78 W / mK and 42.88 W / mK, respectively.

[0113] Embodiment 11

[0114] HfB 2 Powder, SiC powder and BN powder are used as raw materials and the ingredients are prepared according to equation (11).

[0115] The sample phase composition (volume content) is 71% BN-18% HfB 2 -11% SiC.

[0116] Anhydrous ethanol and zirconium oxide balls were used as ball milling media. 2 After the three powders of SiC and BN are evenly mixed, they are rotary evaporated, dried, ground and sieved, and finally poured into a hot-pressed graphite mold. The inner wall of the mold sleeve and the powder are separated by a 0.2mm thick graphite paper. During hot-pressing sintering, the pressure applied to the sample is 40MPa, the sample is heated to 2000℃ at a rate of 10℃ / min, and maintained at 2000℃ and 40MPa for 90min. Finally, the pressure is reduced to 3MPa and the heating is stopped. The sample is cooled to room temperature with the furnace. The relative density of the obtained ceramic is 98.8%, and the hBN grain orientation index is 0.91. When the cutting angle θ is 30°, the room temperature bending strength of the sample in the radial and longitudinal directions is 355±14MPa and 338±21MPa, respectively; the room temperature compressive strength of the sample in the radial and longitudinal directions is 462±25MPa and 458±29MPa, respectively; the room temperature conductivity of the sample in the radial and longitudinal directions is 3.52×10 5 S / m and 4.32×10 5 S / m; the room temperature thermal conductivity of the sample in the radial and longitudinal directions is 72.25W / mK and 41.75W / mK respectively; the electrical conductivity and thermal conductivity of the sample in the radial and longitudinal directions at different temperatures are as follows Figure 3 shown.

[0117] According to the BN-based ceramics prepared in the above embodiment, the maximum difference between the longitudinal and radial bending strengths of the sample at room temperature does not exceed 20 MPa, and the maximum difference between the compressive strengths does not exceed 22 MPa, achieving consistent mechanical properties; the longitudinal and radial electrical and thermal conductivities of the sample show significant differences ( Figure 2-Figure 3 ).

[0118] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A hexagonal boron nitride-based ceramic having consistent mechanical properties in the longitudinal direction and radial direction but significantly different physical properties and a preparation method thereof, characterized in that: C powder, Al powder, B powder, Si powder, BN powder, MN powder, ZrO2 powder, Al2O3 powder, MC powder, MSi2 powder, B4C powder, MB2 powder, SiC powder, Si3N4 powder are used as raw materials, and the proportion of the powder raw materials is determined according to any one of the following chemical reaction equations (1) to (11): 3MN+Al+8B+5.98BN=3MB2+AlN+7.98BN (1)4MN+3Si+4B4C+3BN=3MB2+3SiC+7BN (2) Si3N4+2C+B4C+BN=3SiC+5BN (3) MN+3B+3BN=MB2+4BN (4) MSi2+5BN=MSi2+5BN (5) MC+6BN=MC+6BN (6) ZrO2+4BN=ZrO2+4BN (7) Al2O3+4BN=Al2O3+4BN (8) Si3N4+6BN=Si3N4+6BN (9) SiC+5BN= SiC+5BN (10) MB2+SiC+7BN=MB2+SiC+7BN (11) Wherein, M is selected from any one of Zr, Hf, Nb, Ta, Ti, W, V, Cr and Mo.

2. The hexagonal boron nitride-based ceramic having consistent mechanical properties in the longitudinal direction and radial direction but significantly different physical properties according to claim 1, characterized in that: The average particle size of the MN powder is 0.5-10 μm, and the purity is >95%; the average particle size of the B4C powder is 1-10 μm, and the purity is >95%; the average particle size of the Si powder is 0.5-5 μm, and the purity is >95%; the average particle size of the ZrO2 powder is 0.5-10 μm, and the purity is >95%; the average particle size of the Al2O3 powder is 0.5-5 μm, and the purity is >95%; the average particle size of the Al powder is 0.1-10 μm, and the purity is >95%; the average particle size of the MC powder is 0.5-10 μm, and the purity is >95%; The average particle size of the B powder is 0.2-10μm, and the purity is ≥95%; the average particle size of the BN powder is 1-10μm, and the purity is >95%; the average particle size of the MB2 powder is 0.2-10μm, and the purity is >95%; the average particle size of the MSi2 powder is 0.5-10μm, and the purity is >95%; the average particle size of the SiC powder is 0.5-10μm, and the purity is >95%; the average particle size of the Si3N4 powder is 0.2-10μm, and the purity is >95%; the average particle size of the C powder is 0.5-10μm, and the purity is >95%.

3. A method for preparing a hexagonal boron nitride-based ceramic having consistent mechanical properties in the longitudinal direction and radial direction but significantly different physical properties as claimed in claim 1 or 2, characterized in that: The following steps are involved: Step 1: Accurately mix the powder raw materials according to the chemical reaction equation; The proportioned powders are uniformly mixed, dried, ground and sieved to obtain sintered raw material powders; Step 2: Spark plasma sintering or hot pressing sintering, calculate the weight of the required sintered powder according to the required sample thickness, pour the sieved powder into the corresponding graphite mold, and sinter in a vacuum environment to obtain a cylindrical sintered body containing hexagonal boron nitride-based ceramics; Step 3: After sintering is completed, the cylindrical sintered body is cut into elliptical cylindrical samples according to the preset angle θ, and then the horizontally placed elliptical cylindrical samples are further processed along the longitudinal and radial directions to obtain hexagonal boron nitride-based ceramic products of preset shape and size, wherein the preset angle θ is 0°<θ<90°.

4. The method for preparing hexagonal boron nitride-based ceramics having consistent mechanical properties in the longitudinal direction and radial direction but significantly different physical properties according to claim 3, characterized in that: In the step 1, anhydrous ethanol and zirconium oxide balls are used as ball milling media, and the mass ratio of powder to ball is 1:(1.5-2). The proportioned powder is evenly mixed for 20-30 hours, and the slurry after rotary evaporation is dried in a vacuum drying oven at 50-70° C., and the sintered raw material powder is obtained after grinding and sieving.

5. The method for preparing hexagonal boron nitride-based ceramics having consistent mechanical properties in the longitudinal direction and radial direction but significantly different physical properties according to claim 3, characterized in that: In the step 2, the thickness of the sintered sample is 20 to 40 mm.

6. The method for preparing a hexagonal boron nitride-based ceramic having consistent mechanical properties in the longitudinal direction and radial direction but significantly different physical properties according to claim 3, characterized in that: In the step 2, the sintering temperature ranges from 1400°C to 2000°C.

7. The method for preparing hexagonal boron nitride-based ceramics having consistent mechanical properties in the longitudinal direction and radial direction but significantly different physical properties according to claim 3, characterized in that: In the step 2, the sintering heating rate is 10-300°C / min.

8. The method for preparing hexagonal boron nitride-based ceramics having consistent mechanical properties in the longitudinal direction and radial direction but significantly different physical properties according to claim 3, characterized in that: In the step 2, the pressure applied by the sintering equipment is 20-200 MPa.

9. The method for preparing hexagonal boron nitride-based ceramics having consistent mechanical properties in the longitudinal direction and radial direction but significantly different physical properties according to claim 3, characterized in that: In the step 2, the sintering holding time is 5 to 90 minutes.

10. The method for preparing a hexagonal boron nitride-based ceramic having consistent mechanical properties in the longitudinal direction and radial direction but significantly different physical properties according to any one of claims 5 to 9, characterized in that: In the step 2, the orientation index of the BN grains in the cylindrical sintered body is not less than 0.9.